The Wawel copy of the full code of the Grand Duchy of Lithuania state chronicle-writing: orthographic aspect of research - Mikhalchuk, Hanna N.; Tsivanova, Halina K. (Journal of the Belarusian State University. Philology, 2019)
In the article orthographic peculiarities of the Wawel copy are analysed. The Wawel copy is a copy of the full code of the Grand Duchy of Lithuania state chronicle-writing named after its place of storage. The Wawel copy is textologically close to the Bychaviec Chronicle and is the only Cyrillic copy of the full code known today. The creation of the manuscript dates back to the 2nd part of the XVI century. In the first part of the article the general description of the work is given. The presence of several kinds of handwriting in the manuscript is noted. Examples of passages written in handwritings different from the main handwriting are given. Types of changes in handwriting are analysed, and the conclusion is made that functional division of labour had been existing in-between copyists. In the second part of the article the description of the Wawel copy’s orthographic peculiarities is given. The variability of ways of writing when a copyist reproduced Eastern Slavic and essentially Belarusian phonetic traits is analysed. Break with the bookish Slavonic tradition through phonetic and hyper-normative spelling is demonstrated. The examples of copyist’s individual orthographic norm and sporadic cases of phonetic Polish influences are noted. The conclusion is made that scriptors’ spelling was influenced by their contemporaries’ colloquial enunciation.